Assessment of noise and perception on the mMain roads of vehicular traffic in the city of Ilo, Peru - Balmaceda Flores, Carlos Anthony (2024)
Vehicular noise (VN) constitutes an undesirable sound in urban environments, acting as a disruptive and contaminating agent to human health, affecting both the physical and psychological well-being of individuals. This study aimed to determine the level of VN in key areas of the city of Ilo and assess its impact on the perception of the local population. The methodology employed was the National Environmental Noise Monitoring Protocol, conducting measurements over 21 days, taking into account climatic factors. The noise analysis was carried out using a BSWA 308 Class 1 sound level meter, following national regulations and utilizing maps and variograms to evaluate the spatial and temporal distribution of VN. Furthermore, a survey was employed as a data collection instrument to assess people's perception. During peak hours (12:00 p.m. to 2:00 p.m. and 5:00 p.m. to 7:00 p.m.), it was determined that the sound pressure levels exceeded 70 dB in four sampling points, surpassing environmental quality standards for commercial areas. Areas with higher acoustic contamination exhibited variations in sound pressure levels. Additionally, it is concluded that VN pollution significantly impacts the perception and well-being of the population, manifesting in effects such as headaches, stress, and concentration difficulties. These results emphasize the need to address vehicular congestion and develop mitigation strategies in urban areas to enhance the quality of life for the population.